The law in the land of mirrors: edges and overflows - Wolfzun, Nora (2021)
In the context of a merciless pandemic, a virus interpellates us, in a mirror, showing us what we are, what we protect, and what we abandon. Our proposal to «read the law» in Edgar Allan Poe’s «The Masque of the Red Death» consists of an interrogation of the (im)possibilities of legality in the face of a situation of exceptionality that poses unprecedented challenges. The right «shows» itself through the way it organizes itself to confront the «virus» that threatens it (the virus, the stranger, the other). This is done by putting into action its pre-existing fantasies of protection and abandonment and rehearsing other possible ones. Reading law in literature means entering a field of unprecedented freedoms. The literature presents itself as an enigma, disempowerment, and resistance to the canonical. It will produce an overflow in the legal discourse. This approach allows it to critically subvert its foundations and broaden its horizons of meaning. Literature «reminds» law of the poiética and political dimension of language.